Targeting the Tumour: Cell Penetrating Peptides for Molecular Imaging and Radiotherapy - Kersemans, Veerle (Molecular Diversity Preservation International, 2010)
Over the last couple of years, the number of original papers and reviews discussing various applications of cell penetrating peptides (CPPs) has grown exponentially. This is not remarkable since CPPs are capable of transporting the most varying cargo across cell membranes which is one of the biggest problems in drug delivery and targeted therapy. In this review, we focus on the use of CPPs and related peptides for delivery of imaging contrast agents and radionuclides to cells and tissues with the ultimate goal of in vivo molecular imaging and molecular radiotherapy of intracellular and even intranuclear targets.